Investigation of the effects of NF-kB on ota induced apoptosis in HK-2 cell line - Gürkaşlar, Can. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
Ocharoxin A (OTA) is a mycotoxin produced by certain species of Aspergillus and Peni cillium genera of fungi. OTA was shown to be carcinogenic, genotoxic, immunotoxic by many studies and main suspected causative agent for Balkan Endemic Nephropathy. OTA induces oxidative stress, causes cell cycle arrest and deregulates various signaling pathways. There is no study relating the NFκB activity and apoptosis upon OTA treatment. In this study, we have shown that OTA induces canonical NF-κB pathway in HK-2 cells. OTA mediates nuclear translocation of p65 subunit of NF-κB as well as NF-κB-driven gene expression. Moreover, We observed that, when NF-κB pathway was inhibited by Bay11-7085 OTA-induced Erk1-2 phosphorylation was diminished. Our results suggest that NF-κB inhibition also abate Erk1-2 mediated apoptosis upon OTA treatment. Finally, we have generated K310R-RelA HK-2 cell line expressing dominant-negative form of p65 subunit of NF-κB. Prolonged OTA exposure of these cells decreased Erk1-2 phosphorylation compared to control cells. However, the sup pression of OTA-induced apoptotic cell death observed with chemical inhibition of NF-κB could not be achieved with this stable cell line. In conclusion, our results shed light on another major pathway aﬀected by OTA and disclose one of the missing steps in OTA mode of action and relate it with foreknown eﬀects of OTA, Erk1-2 phospho rylation and induction of apoptosis.
Keywords: Ochratoxin.